Mating of Discrete Trees and Walks in the Quarter-Plane - Biane, Philippe (The Electronic Journal of Combinatorics, 2021)
We give a general construction of triangulations starting from a walk in the quarter plane with small steps, which is a discrete version of the mating of trees. We use a special instance of this construction to give a bijection between maps equipped with a rooted spanning tree and walks in the quarter plane. We also show how the construction allows to recover several known bijections between such objects in a uniform way.